2017
DOI: 10.1177/0961000617742458
|View full text |Cite
|
Sign up to set email alerts
|

Choice of career in library and information science and past work experience

Abstract: The study explores how different occupational backgrounds of Master’s students in LIS shape their motivation to choose a career in the library profession. The research is conducted on full-time employed Master’s students from Hong Kong. The research method applied is survey, and data were collected with an online questionnaire. The study reveals that students with library jobs significantly differ from students employed elsewhere with respect to motivation to pursue a career in LIS. While library-employed stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Because of the distinctive colonial pasts, sociocultural, and information landscapes amongst the three regions, the professional qualification, requirements, and practices for LIS professionals in Hong Kong, Taiwan, and Mainland China are distinctively different from one another (Dukic, 2017; Ho et al, 2018; Lo et al, 2015, 2017). These differences are further reflected in the LIS curricula at all three universities in this study.…”
Section: Technical Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the distinctive colonial pasts, sociocultural, and information landscapes amongst the three regions, the professional qualification, requirements, and practices for LIS professionals in Hong Kong, Taiwan, and Mainland China are distinctively different from one another (Dukic, 2017; Ho et al, 2018; Lo et al, 2015, 2017). These differences are further reflected in the LIS curricula at all three universities in this study.…”
Section: Technical Limitationsmentioning
confidence: 99%
“…Furthermore, according to the findings of our previous studies, a significant percentage of LIS students at both HKU (41.7%) and NTNU (22.8%) already held graduate-level qualifications (in other non-LIS-related academic disciplines) prior to entering the MLIS program. For this reason, students at both HKU and NTNU tended to vary widely in terms of their educational and occupational backgrounds (Dukic, 2017; Ho et al, 2016; Lo et al, 2015, 2017). In comparison, only a small number (3%) of PKU students held postgraduate qualifications prior to entering the MLIS program (Ho et al, 2016).…”
Section: Technical Limitationsmentioning
confidence: 99%
“…In general, career decisions for undergraduate students are motivated by demographic, social, environmental, and cultural factors (Thomas et al, 2023). However, many prospective LIS professionals enter an MLIS program as a second or even third career (Ard, 2006;Beck & Callison, 2006;Dukic, 2019) and for many it is not their first choice for a graduate program (Ho et al, 2018). In particular, Taylor et al (2011) found that over half of MLIS students decided on LIS after completing their first degree, and a third made the call more than five years after completing their first degree.…”
Section: Motivations To Enter Mlis Program and Lis Professionsmentioning
confidence: 99%
“…In particular, Taylor et al (2011) found that over half of MLIS students decided on LIS after completing their first degree, and a third made the call more than five years after completing their first degree. There is a noted increase in second-career librarians coming from other occupational areas (Dukic, 2019), and Canada leads this trend (Lo et al, 2015). Entering into the field of LIS professions is often considered serendipitous or accidental (Hallmark & Lembo, 2003).…”
Section: Motivations To Enter Mlis Program and Lis Professionsmentioning
confidence: 99%
See 1 more Smart Citation